DEVELOPMENT OF TECHNOLOGY FOR PRODUCTION OF SEMI-FINISHED PRODUCTS BASED ON VEGETABLE RAW MATERIALS WITH A HIGH CONTENT OF ANTIOXIDANTS AND Р-CAROTENE - N. V. Makarova; D. F. Ignatova; Y. S. Kudusova (Современная наука и инновации, 2022)
Vegetables play an important role in the human diet. They saturate the body with vitamins, minerals, dietary fibers, etc. in Addition, some vegetables contain antioxidant substances that protect the human body from the effects offree radicals, thereby increasing immunity, contribute to the body's resistance to the influence of negative environmental factors. But despite this, their use in the food industry is limited. In this regard, a promising direction is the use of vegetable puree in the production of confectionery.